Recurrent de novo mitochondrial DNA mutations in respiratory chain deficiency. Issue 12 (18th December 2003) - Lebon, S; Chol, M; Benit, P; Mugnier, C; Chretien, D; Giurgea, I; Kern, I; Girardin, E; Hertz-Pannier, L; de Lonlay, P; Rötig, A; Rustin, P; et al.
Abstract : Starting from a cohort of 50 NADH-oxidoreductase (complex I) deficient patients, we carried out the systematic sequence analysis of all mitochondrially encoded complex I subunits (ND1 to ND6 and ND4L) in affected tissues. This approach yielded the unexpectedly high rate of 20% mutation identification in our series. Recurrent heteroplasmic mutations included two hitherto unreported (T10158C and T14487C) and three previously reported mutations (T10191C, T12706C and A13514G) in children with Leigh or Leigh-like encephalopathy. The recurrent mutations consistently involved T→C transitions (p<10 −4 ). This study supports the view that an efficient molecular screening should be based on an accurate identification of respiratory chain enzyme deficiency.